2022
DOI: 10.3389/fnhum.2021.796799
|View full text |Cite
|
Sign up to set email alerts
|

Time Interaction With Two Spatial Dimensions: From Left/Right to Near/Far

Abstract: In this study, we explored the time and space relationship according to two different spatial codings, namely, the left/right extension and the reachability of stimulus along a near/far dimension. Four experiments were carried out in which healthy participants performed the time and spatial bisection tasks in near/far space, before and after short or long tool-use training. Stimuli were prebisected horizontal lines of different temporal durations in which the midpoint was manipulated according to the Muller-Ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 83 publications
3
1
0
Order By: Relevance
“…To explore how participants performed the timeestimation task, we conducted a one-way ANOVA on the mean reproduced times with intervals (1,600, 1,800, 2,000, 2,200, or 2,400 ms) as within-subjects factors. As expected, there was a main effect of time interval, F( 4 the intervals differed between themselves (p < .01 for all comparisons), demonstrating that participants were accurate at discriminating between different intervals, which is consistent with findings of previous studies (Candini et al, 2022;Frassinetti et al, 2009;Magnani et al, 2013).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…To explore how participants performed the timeestimation task, we conducted a one-way ANOVA on the mean reproduced times with intervals (1,600, 1,800, 2,000, 2,200, or 2,400 ms) as within-subjects factors. As expected, there was a main effect of time interval, F( 4 the intervals differed between themselves (p < .01 for all comparisons), demonstrating that participants were accurate at discriminating between different intervals, which is consistent with findings of previous studies (Candini et al, 2022;Frassinetti et al, 2009;Magnani et al, 2013).…”
Section: Resultssupporting
confidence: 90%
“…As expected, there was a main effect of time interval, F (4, 116) = 69.999, p < .0001, η p 2 = .707; participants’ time estimates increased as a function of the time intervals. Crucially, Bonferroni-Holm correction revealed that all the intervals differed between themselves ( p < .01 for all comparisons), demonstrating that participants were accurate at discriminating between different intervals, which is consistent with findings of previous studies (Candini et al, 2022; Frassinetti et al, 2009; Magnani et al, 2013).…”
Section: Resultssupporting
confidence: 90%
“…We interpreted the improvement toward the Past as a selective effect of the leftward shift of spatial attention induced by PA. This evidence is consistent with the well-known spatial representation of time (Anelli et al, 2015, 2016b; Bonato et al, 2012; Candini et al, 2022; Magnani et al, 2014, 2021). Further support for the interpretation of visuospatial modulations of PA on MTT comes from the finding that exposure to neutral lenses did not change participants’ performance (Control Experiment).…”
Section: Discussionsupporting
confidence: 90%
“…This article is intended solely for the personal use of the individual user and is not to be disseminated broadly. PRISM EFFECTS ON MENTAL TIME TRAVEL NETWORK spatial representation of time (Anelli et al, 2015(Anelli et al, , 2016bBonato et al, 2012;Candini et al, 2022;Magnani et al, 2014Magnani et al, , 2021. Further support for the interpretation of visuospatial modulations of PA on MTT comes from the finding that exposure to neutral lenses did not change participants' performance (Control Experiment).…”
Section: Discussionmentioning
confidence: 96%